A case in which the tip of a plastic stent placed to prevent recurrence of walled‐off necrosis penetrated the bile duct and formed a stent–stone complex. Issue 1 (28th March 2023) - Sakuma, Fumi; Irisawa, Atsushi; Noguchi, Satoaki; Abe, Yoko; Hoshi, Koki; Yamamiya, Akira; Nagashima, Kazunori; Kashima, Ken; Kunogi, Yasuhito; Fukushi, Koh; Inaba, Kohei; Oike, Ken; et al.
Abstract: A woman in her 60s underwent endoscopic sphincterotomy for choledocholithiasis. Unfortunately, post‐endoscopic retrograde cholangiopancreatography pancreatitis occurred. In addition, huge walled‐off necrosis (WON) appeared as a late complication. For the infected WON, endoscopic ultrasound‐guided fistuloplasty and endoscopic necrosectomy were performed, and a double pigtail plastic stent (PS) (7Fr, 7 cm) was placed to prevent a recurrence. Plain computed tomography conducted two years later showed that the stent implanted for WON had deviated. The distal end of the stent was found to have migrated into the bile duct. In addition, common bile duct stones with stents as nuclei were observed. Upon performing endoscopic retrograde cholangiography, it was revealed that the stent tip perforated the distal bile duct just above the papilla. After removal of the stent using grasping forceps, we made an incision between the duodenal – bile duct fistula and bile duct orifice using a sphincterotome. Then, the stone was removed by a balloon catheter. Although such late adverse events are rare occurrences, placement of long‐term PS after treatment of WON should be followed up regularly with imaging examination, and if there is no recurrence for several months, removal of the PS at that point may be considered.